2011
DOI: 10.1603/ec11104
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Heat Treatment for Disinfestation of Concrete Grain Silos

Abstract: Field experiments were conducted in 2007 and 2008 to evaluate heat treatment for disinfestations of empty concrete elevator silos. A Mobile Heat Treatment Unit was used to introduce heat into silos to attain target conditions of 50ЊC for at least 6 h. Ventilated plastic containers with a capacity of 100 g of wheat, Triticum aestivum L., held Rhyzopertha dominica (F.) (Coleoptera: Bostrichidae) and Tribolium castaneum (Herbst) (Coleoptera: Tenebrionidae). Polyvinyl chloride containers with a capacity of 300 g o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…For example, observation of L. entomophila in tobacco-processing buildings on farms in Zimbabwe (49) showed a significant drop in psocid numbers once the humidity and temperature levels in the storage structure were kept below 70% RH and 18 • C, respectively. (69). Heat was applied to the silos with the aim of achieving 49 • C for 6 h in all parts of the structure.…”
Section: Drying and Coolingmentioning
confidence: 99%
“…For example, observation of L. entomophila in tobacco-processing buildings on farms in Zimbabwe (49) showed a significant drop in psocid numbers once the humidity and temperature levels in the storage structure were kept below 70% RH and 18 • C, respectively. (69). Heat was applied to the silos with the aim of achieving 49 • C for 6 h in all parts of the structure.…”
Section: Drying and Coolingmentioning
confidence: 99%
“…High temperatures used for disinfestation may cause disruption of structural integrity and affect other qualities of the treated commodities. Scaling up of these heat treatment methods to an industrial level can be complex, time‐consuming, and expensive (Hansen et al., 2011; Opit, Jones, Bonjour, Arthur, & Phillips, 2011). Mahroof, Subramanyam, Throne, and Menon (2003) suggested that a temperature of 50 °C for 24 hr is enough to kill all life stages of major stored pests in postharvest agricultural commodities.…”
Section: Existing Disinfestation Techniquesmentioning
confidence: 99%
“…Opit et al. (2011) used high‐temperature treatment to disinfest grain silos and containers and suggested that proper precleaning of storages can append the effectiveness. Heat treatments are usually performed for grain storage structures, generally by hot water for removal of particles, husks, and insect fragments.…”
Section: Existing Disinfestation Techniquesmentioning
confidence: 99%
“…The success of these treatments is dependent upon obtaining temperatures of about 50°C throughout the facilities. As product residues have been shown to insulate pest insects from the heat, sanitation of the facilities before treatment is very important (Brijwani et al 2010, Opit et al 2011.…”
Section: Mebr Alternatives For Postharvest Structural and Qps Applicmentioning
confidence: 99%